Urinary tract infection: searching evidence for nursing care. - Roberto Santos Oliveira; Neusa Maria de Azevedo; Isabel Cristina Fonseca da Cruz; Marilda Andrade; Fatima Helena do Espirito Santo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
<!-- /* Font Definitions */ @font-face {font-family:Wingdings; panose-1:5 0 0 0 0 0 0 0 0 0; mso-font-charset:2; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:0 268435456 0 0 -2147483648 0;} @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1593833729 1073750107 16 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} h1 {mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:1; font-size:10.0pt; font-family:Arial; mso-bidi-font-family:"Times New Roman"; mso-font-kerning:0pt; layout-grid-mode:line; mso-bidi-font-weight:normal;} p.MsoFooter, li.MsoFooter, div.MsoFooter {margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; tab-stops:center 220.95pt right 441.9pt; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line;} p.MsoBodyTextIndent, li.MsoBodyTextIndent, div.MsoBodyTextIndent {margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:42.55pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line;} p.MsoBodyText2, li.MsoBodyText2, div.MsoBodyText2 {margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line; font-style:italic; mso-bidi-font-style:normal;} p.MsoBodyText3, li.MsoBodyText3, div.MsoBodyText3 {margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line; font-style:italic; mso-bidi-font-style:normal;} p.MsoBodyTextIndent2, li.MsoBodyTextIndent2, div.MsoBodyTextIndent2 {margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:42.55pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line; font-style:italic; mso-bidi-font-style:normal;} a:link, span.MsoHyperlink {color:blue; text-decoration:underline; text-underline:single;} a:visited, span.MsoHyperlinkFollowed {color:purple; text-decoration:underline; text-underline:single;} span.Hiperlink {mso-style-name:Hiperlink; mso-style-parent:""; color:blue; text-decoration:underline; text-underline:single;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} /* List Definitions */ @list l0 {mso-list-id:268052125; mso-list-type:hybrid; mso-list-template-ids:70316294;} @list l0:level1 {mso-level-number-format:bullet; mso-level-text:o; mso-level-tab-stop:36.0pt; mso-level-number-position:left; text-indent:-18.0pt; font-family:"Courier New";} @list l0:level2 {mso-level-tab-stop:72.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level3 {mso-level-tab-stop:108.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level4 {mso-level-tab-stop:144.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level5 {mso-level-tab-stop:180.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level6 {mso-level-tab-stop:216.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level7 {mso-level-tab-stop:252.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level8 {mso-level-tab-stop:288.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l0:level9 {mso-level-tab-stop:324.0pt; mso-level-number-position:left; text-indent:-18.0pt;} @list l1 {mso-list-id:362904726; mso-list-type:simple; mso-list-template-ids:68550669;} @list l1:level1 {mso-level-number-format:bullet; mso-level-text:; mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt; font-family:Wingdings;} @list l2 {mso-list-id:626811382; mso-list-type:simple; mso-list-template-ids:-1042898894;} @list l2:level1 {mso-level-start-at:0; mso-level-number-format:bullet; mso-level-text:-; mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt; font-family:"Times New Roman";} @list l3 {mso-list-id:1247570772; mso-list-type:simple; mso-list-template-ids:68550671;} @list l3:level1 {mso-level-start-at:5; mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt;} @list l4 {mso-list-id:1473055132; mso-list-type:simple; mso-list-template-ids:-1896568314;} @list l4:level1 {mso-level-start-at:6; mso-level-number-format:bullet; mso-level-text:-; mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt; mso-ansi-font-style:normal;} @list l5 {mso-list-id:1945960859; mso-list-type:simple; mso-list-template-ids:68550671;} @list l5:level1 {mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt;} @list l6 {mso-list-id:2108503281; mso-list-type:simple; mso-list-template-ids:-2084043546;} @list l6:level1 {mso-level-tab-stop:18.0pt; mso-level-number-position:left; margin-left:18.0pt; text-indent:-18.0pt; color:black; mso-ansi-font-weight:normal;} ol {margin-bottom:0cm;} ul {margin-bottom:0cm;} -->  <!-- /* Font Definitions */ @font-face {font-family:Wingdings; panose-1:5 0 0 0 0 0 0 0 0 0; mso-font-charset:2; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:0 268435456 0 0 -2147483648 0;} @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1593833729 1073750107 16 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} h1 {mso-style-next:Normal; margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; page-break-after:avoid; mso-outline-level:1; font-size:10.0pt; font-family:Arial; mso-bidi-font-family:"Times New Roman"; mso-font-kerning:0pt; layout-grid-mode:line; mso-bidi-font-weight:normal;} p.MsoFooter, li.MsoFooter, div.MsoFooter {margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; tab-stops:center 220.95pt right 441.9pt; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line;} p.MsoBodyTextIndent, li.MsoBodyTextIndent, div.MsoBodyTextIndent {margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:42.55pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; layout-grid-mode:line;} p.MsoBodyText2, li.MsoBodyText2, div.MsoBodyText2 {margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman";